2021
DOI: 10.21608/ejp.2021.77853.1035
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Variation and Molecular Characterization of Macrophomina phaseolina, the Cause of Sesame Charcoal Rot

Abstract: Macrophomina phaseolina (Tassi) Goid is one of the most important soil-borne fungi that affects sesame and causes charcoal rot disease, with a great economic challenge to sesame growers worldwide. Pathogenic and molecular characterizations of eleven M. phaseolina isolates collected from different geographical regions in Egypt were carried out to determine the pathogenicity and genetic diversity. Pathogenicity tests showed a pathogenic variability among the isolates. The identification of M. phaseolina isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…In the present study, results have shown a high level of polymorphism among M. phaseolina populations of sesame with different geographical origins using neutral ISSR marker in southern Iran. These findings are consistent with previous studies (Aghakhani and Dubey, 2009;Khamari et al, 2023;Khamari et al, 2022;Linhai et al, 2011;Yousef, 2021) that have demonstrated high genetic diversity of M. phaseolina is reflected not only in isolates from different hosts but also within isolates collected from a special host or geographical origin. In general, high genetic diversity levels among a large collection of M. phaseolina populations could be attributed to parasexual recombination between nuclear genes or fusion of vegetative cells favoring heterokaryons, this is corroboration with earlier studies (Carlile, 1986).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, results have shown a high level of polymorphism among M. phaseolina populations of sesame with different geographical origins using neutral ISSR marker in southern Iran. These findings are consistent with previous studies (Aghakhani and Dubey, 2009;Khamari et al, 2023;Khamari et al, 2022;Linhai et al, 2011;Yousef, 2021) that have demonstrated high genetic diversity of M. phaseolina is reflected not only in isolates from different hosts but also within isolates collected from a special host or geographical origin. In general, high genetic diversity levels among a large collection of M. phaseolina populations could be attributed to parasexual recombination between nuclear genes or fusion of vegetative cells favoring heterokaryons, this is corroboration with earlier studies (Carlile, 1986).…”
Section: Discussionsupporting
confidence: 93%
“…To the best of our knowledge, the present work is a study of population structure of a large collection of M. phaseolina isolates collected from five different climatic regions in Iran; temperate with mild winters (Fars and Kogiluyeh & Boyer-Ahmad provinces), warm and dry winter (Khuzestan province), and warm, dry with cool winter (Bushehr and Hormozgan provinces). ISSR marker has been extensively used for assessing variation within and among M. phaseolina species (Khamari et al, 2023;Khamari et al, 2022;Mahdizadeh et al, 2012;Salahlou et al, 2016;Yousef, 2021). In the present study, results have shown a high level of polymorphism among M. phaseolina populations of sesame with different geographical origins using neutral ISSR marker in southern Iran.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation